Linear buckling of an axially reinforced pressurised cylinder - Houghton, D. S.; Johns, D. J. (College of Aeronautics, 1960)
An analysis is presented using small deflection theory for the buckling of a pressurised, axially reinforced cylinder, which is subjected to axial compression. Various approximations to the analysis are discussed and some results are presented which show the effects of internal pressure and various structural parameters on both panel buckling and overall buckling.